Toward the Identification of Extra-Oral TAS2R Agonists as Drug Agents for Muscle Relaxation Therapies via Bioinformatics-Aided Screening of Bitter Compounds in Traditional Chinese Medicine - Luo, Mingzhi; Ni, Kai; Jin, Yang; Yu, Zifan; Deng, Linhong (Frontiers in Physiology, 2019)
Significant advances have been made in the past decade in mapping the distributions and the physiological functions of extra-oral TAS2Rs in non-gustatory tissues. TAS2Rs are expressed in muscle cells such as smooth muscle, heart muscle, and skeletal muscle and the activation of TAS2Rs couples to the relaxation of different kinds of muscles. Traditional Chinese medicines (TCM) are divided into five different flavors including “bitter flavor” according to their taste and functions. Many of bitter flavors have been proved the capability to relax muscle cells by long term using and experiments. Experiments also indicate that bitter tasting components identified from bitter flavors activate TAS2Rs and relax muscle. Therefore, TAS2Rs maybe general therapy targets for screening relaxation agonists of muscle from bitter flavors of TCM. We reviewed the distribution of TAS2Rs in muscle systems and focused on the map of bitter flavors which can regulate the contractility of muscles and related functional chemical components. We also reviewed the recently established databases about TCM and their components and software which can be used for bioinformatics mining of bitter flavors to develop new muscle relaxants. Screening and identification of new muscle relaxants via TAS2Rs signaling from bitter flavors of TCM may be a new way to discover novel therapy medicines for relaxing muscle system.